Alaska 2026 - St. Louis, Regis; Burdette, Melody; Raub, Kevin; Vorhees, Mara (Lonely Planet guidebooks., 2026)
Discover Alaska's most popular experiences and best kept secrets from looking for grizzly brown bears on the Denali Park Road, to kayaking in the rugged wilderness of Resurrection Bay, and visiting the Alaska Folk School in Fairbanks for classes in everything from woodworking to cabin construction.